MRI Findings and Serum Creatine Kinase Correlation in Inflammatory Myopathies - Sunia Hameed, Aisha Mumtaz, Azka Rehman Alavi, Zahid Nazir, Noor-un-Nisa Memon, Muhammad Faisal Bashir, Patel Khushbu Komalbhai, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Inflammatory myopathies area heterogeneous group of muscle disorders characterized by muscle inflammation,weakness, and elevated muscle enzymes.